AB0811-PC Efficacy and safety of certolizumab pegol with methotrexate in rheumatoid arthritis patients. (23rd January 2014) - Carlino, G.; Cozzolongo, A.; Maggio, R.
Abstract : Background: Certolizumab Pegol (CZP), administered every 2 weeks in combination with Methotrexate (MTX), showed rapid efficacy and had an acceptable safety profile in patients(pts) with RA in several clinical trials. Objectives: To confirm the efficacy and safety of CZP+MTX in pts with active RA and an previous inadequate response to MTX. Methods: In this study 17 pts [mean age±DS:50±7.1 years (min-max 38-62)] with active RA [CRP: 11.1±5.7 mg/L (6.3-24), ESR: 38.9±12.6 (24-67) mm/h, DAS28(ESR): 4.7±0.4 (4.1-5.2), HAQ: 1.9±0.3 (1, 0-2.3)] received CZP every two weeks (Wks) [a dose of 400mg for the first three times (at Wks 0, 2 and 4) followed by 200mg] and a stable dose of MTX (10-20 mg/Wk) for 52 weeks. Results: 16 pts completed the study, because a case of pancytopenia determined the discontinuation of the drug in one pt. This was the only adverse event. DAS28(ESR) was significantly lower after 52 Wks (P=0.00013). HAQ, pain and global disease activity had significantly improved after 52 Wks. In table I is shown the average value of DAS28(ESR), ESR, CRP and HAQ at the beginning of the study (T0) and after 52 Weeks (T52). Image/graph: Conclusions: Use of CZP 200mg (after three initial subministrations of 400 mg) every 2 Wks + MTX resulted in a rapid and sustained reduction of RA signs, symptoms and pain, and improved physical function. CZP had an acceptable safety profile. This confirms the efficacy and safety of CZP in MTX refractary RA. Disclosure of Interest: None Declared